Fault lines : a novel - Itami, Emily (Custom House, 2021)
Combining the incisive intimacy of Sally Rooney with the sharp wit of Helen Fielding, a compulsively readable and astonishingly relatable debut novel about marriage, motherhood, love, self and the vibrant, surprising city that is modern Tokyo. Mizuki is a Japanese housewife. She has a hardworking husband, two adorable children and a beautiful Tokyo apartment. It's everything a woman could want, yet sometimes she wonders whether it would be more fun to throw herself off the high-rise balcony than spend another evening not talking to her husband or hanging up laundry. Then, one rainy night, she meets Kiyoshi, a successful restaurateur. In him, she rediscovers freedom, friendship, a voice, and the neon, electric pulse of the city she has always loved. But the further she falls into their relationship, the clearer it becomes that she is living two lives - and in the end, we can choose only one. Alluring, compelling, startlingly honest and darkly funny, Fault Lines is a bittersweet love story and a daring exploration of modern relationships from a writer to watch.